Human T‐lymphotropic virus in Irish blood donors: Impact on future testing strategy. Issue 9 (13th July 2022) - Williams, Pádraig; O'Flaherty, Niamh; Field, Stephen; Waters, Allison
Abstract: Aim: A risk‐based approach to the testing of blood donations for Human T‐Lymphotropic Virus (HTLV) should include an assessment of blood donation seroepidemiology. The objectives of the present study were to determine the proportion of HTLV positive units in Irish blood donations, and subsequently, to estimate the current risk of transfusion transmitted HTLV (TT‐HTLV). Methods: Over 3 million donations screened between 1996 and 2020, were included in the study ( n  = 3, 666, 253). Factors considered in the assessment of TT‐HTLV risk included: (I) HTLV seropositivity, (ii) probability of a leucodepletion failure, and (iii) the HTLV testing strategy. Results: Six HTLV positive donations were detected throughout the study period, all of them in previously unscreened blood donors (0.000164%; n  = 6/3, 666, 253), 3 of whom had donated prior to the introduction of HLTV antibody testing. On average 0.11% of manufactured blood components assessed, failed to satisfy the leucodepletion quality assurance criteria of less than 1 × 10 6 cells/unit. In using these values to model the risk of TT‐HTLV, it was shown that the combination of leucodepletion with either universal screening of all = donors, or selective testing of first‐time donors, a possible HTLV transfusion transmitted infection would be prevented every 468–3776 years. Conclusions: This is the first report on the proportion of HTLV positive in Irish blood donations (1996–2020) and will be used to inform blood donation screening policy in Ireland. Evidence is provided for recommending a selective HTLV donor screening algorithm in Ireland that is accompanied by a robust framework for continued surveillance of leucodepletion failure rate.